Scleral flaps, pars plana vitrectomy and gore-tex sutured posterior chamber intraocular lens placement: a case series and review of literature - Napolitano, Pasquale; Filippelli, Mariaelena; Carosielli, Marianna; Costagliola, Ciro; Dell’Omo, Roberto (Frontiers in Ophthalmology, 2023)
Introduction: Cataract surgery is one of the most common surgical procedures performed worldwide. Intraocular lens (IOL) implants are placed routinely in the capsular bag after successful cataract extraction. However, in the absence of adequate capsular support, IOL may be placed in the anterior chamber, fixated to the iris or fixated to the sclera. The purpose of this study is to report the clinical outcomes and safety profile of a trans-scleral sutured intraocular lens (IOL) technique using scleral flaps, vitrectomy, and Gore-Tex suture to place posterior chamber IOL. Methods: Retrospective, interventional case series of eyes undergoing scleral fixation of an IOL using Gore-Tex suture with concurrent vitrectomy. Ocular examination with the logarithm of the minimum angle of resolution visual acuity (logMAR BCVA), tonometry, and slit-lamp biomicroscopy was performed on all patients at 1, 3, 6, and 12 months after the operation. All post-operative complications were recorded. Results: Twenty-five eyes of 25 patients were included. Mean logMAR BCVA improved from 0.43 ± 0.36 (20\40 Snellen equivalent) preoperatively to 0.13 ± 0.18 (20\25 Snellen equivalent) postoperatively at 12 months (p<0.01). Indications included surgical aphakia (16) and dislocated lens implant (9). No cases of IOL opacification, suprachoroidal haemorrhage, post-operative endophthalmitis, IOL dislocation, Gore-Tex exposure, or retinal detachment were observed during the follow-up period. Conclusion: Ab externo scleral fixation of IOLs with Gore-Tex suture plus scleral flap is well tolerated and associated with a very low rate of suture exposition. Moreover, our study confirms excellent refractive outcomes after surgery.